The Biogenesis of miRNAs and Their Role in the Development of Amyotrophic Lateral Sclerosis - Liu, Jinmeng; Zhou, Fenghua; Guan, Yingjun; Meng, Fandi; Zhao, Zhenhan; Su, Qi; Bao, Weiwei; Wang, Xuemei; Zhao, Jiantao; Huo, Zijun; Zhang, Lingyun; Zhou, Shuanhu; et al. (Cells (Basel, Switzerland), 2022)
Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects upper and lower motor neurons. As there is no effective treatment for ALS, it is particularly important to screen key gene therapy targets. The identifications of microRNAs (miRNAs) have completely changed the traditional view of gene regulation. miRNAs are small noncoding single-stranded RNA molecules involved in the regulation of post-transcriptional gene expression. Recent advances also indicate that miRNAs are biomarkers in many diseases, including neurodegenerative diseases. In this review, we summarize recent advances regarding the mechanisms underlying the role of miRNAs in ALS pathogenesis and its application to gene therapy for ALS. The potential of miRNAs to target diverse pathways opens a new avenue for ALS therapy.